Integral Operators of Mixed Type of Nonlinear Integral Equation - Lamyaa H. Saadoon (College of Education for Pure Sciences, 2018)
In this paper, we investigate some properties of nonlinear integral operators of mixed type of integral equations with kernels depending on two variables. The results concerning the continuity and compactness of these operators are obtained.